Highly sensitive conductive photoresist compositions and their patterning applications
Patent Information
- Application Number
- CN202511970728.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-24
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2045-12-24
AI Technical Summary
[0008]针对现有技术的缺陷,本发明的目的在于提供一种共轭聚合物光刻胶的直接光刻的方法,以解决现有技术无法突破复杂工艺及微纳尺寸的限制
1. 避免共轭和非共轭部分的微相分离。传统的图案化策略包括侧链交联和引入交联单体等方式,这种策略由于多组分之间在化学结构、极性和构象上的巨大差异,导致其在纳米尺度发生微相分离,最终形成粗糙度增加、边缘锯齿、桥接或断裂等缺陷的图形。本发明通过物理交联构建互穿网络,有效避免了共轭部分和非共轭部分会分开聚集而产生的非均匀性。
Smart Images

Figure CN121742124B_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of photolithography materials, specifically relating to a highly sensitive flexible conductive photoresist composition, its preparation method, and its patterning application. Background Technology
[0002] The delocalization of π electrons in the conjugated backbone of conductive polymers, particularly conjugated organic molecules, enables the formation of "band" structures similar to those in inorganic semiconductors, providing channels for the transport of charges (electrons and holes) between molecules (through π-π stacking). With their tunable electronic structure, excellent optoelectronic properties, and good solution processability, conductive polymers have attracted considerable interest for their potential applications in flexible electronics, bioelectronics, and large-area displays. To achieve high-density integration and miniaturization of these devices, the development of micro / nano fabrication techniques compatible with conductive polymers, especially photolithography, is crucial. Patterning conductive polymer thin films using photolithography is a key step in transforming them from laboratory materials into practical application devices.
[0003] Currently, various strategies have been attempted to apply photolithography to the patterning of conductive polymers, but all have significant limitations. One traditional strategy is the side-chain crosslinking method. This method introduces photocrosslinkable groups (such as cinnamic acid esters, azides, etc.) onto the side chains of the conductive polymer. Under ultraviolet light irradiation, these groups undergo a crosslinking reaction, making the polymer insoluble in the developer, thereby achieving patterning. However, this method has inherent drawbacks: First, the crosslinking reaction usually destroys the π-conjugated structure of the polymer backbone, leading to a significant decrease in the material's conductivity and charge mobility, sacrificing its core electrical properties. Second, designing and synthesizing polymeric monomers with specific photocrosslinked side chains is complex, costly, and limits the diversity of material systems. Another common strategy is to introduce crosslinking monomers, i.e., mixing one or more non-conjugated photocrosslinking agents or polymerizable monomers into the conductive polymer system. During photolithography, these additives react to form a crosslinked network, "fixing" the conductive polymer in the exposed area. However, this method also has problems: the compatibility between the additives and the conductive polymer is difficult to guarantee, and phase separation easily occurs, leading to uneven film and inconsistent performance. Furthermore, these non-conjugated additives are themselves insulating, and their presence in the film hinders charge transport, forming a potential barrier, which also degrades the conductivity of the final pattern.
[0004] More importantly, neither of the above two strategies has solved a fundamental technical obstacle: how to achieve high-sensitivity photolithography while maintaining high electrical conductivity. Conjugated polymer backbones consist of a large number of continuous π-conjugated units, which themselves have very strong intrinsic absorbance in the ultraviolet to visible light range, typically forming dark (e.g., deep red, blue, black) films. When such materials are used as photoresists, their photoactive components (such as crosslinking groups on side chains or mixed crosslinking agents) need to absorb photon energy from ultraviolet light to initiate the desired photochemical reaction. However, in the presence of a strongly conjugated backbone, most of the light energy irradiated to the film surface is absorbed by the conjugated backbone at the surface and dissipated in the form of heat or fluorescence, failing to effectively penetrate deep into the film or be fully utilized by the deep active sites.
[0005] Therefore, the existing technology faces three mutually restrictive technical challenges: (1) the introduction of cross-linking structure easily destroys the conjugated main chain, resulting in a decrease in conductivity; (2) the addition of insulating cross-linking agent causes phase separation and hinders charge transport; (3) the strong light absorption of the conjugated main chain shields the photoactive sites, resulting in extremely low sensitivity.
[0006] As is known to those skilled in the art, improving photolithography sensitivity typically relies on increasing photoinitiation efficiency or improving light energy utilization. However, in conductive polymer systems, any conventional means of attempting to enhance photoresponse (such as increasing photoinitiator content or extending exposure time) will exacerbate phase separation or further reduce conductivity, thus deteriorating overall performance. To date, no existing technology can simultaneously achieve high conductivity, high resolution, high sensitivity, and good flexibility.
[0007] Therefore, there is an urgent need in this field to develop new photoresist materials and micro / nano fabrication methods. One of the goals is to resolve the contradiction between the strong light absorption of the conjugated backbone and the light energy required by the photoactive groups. This is not only a requirement for improving processing efficiency and reducing energy consumption, but also key to achieving high-precision patterning and promoting the application of conjugated polymers in next-generation microelectronic devices. Summary of the Invention
[0008] In view of the shortcomings of the prior art, the purpose of this invention is to provide a direct photolithography method for conjugated polymer photoresists, so as to solve the limitations of the prior art in overcoming the complex process and micro-nano size.
[0009] On one hand, this disclosure provides a photoresist composition, characterized in that the photoresist composition comprises a compound of formula I and a compound of formula II: (I) (II) In Formula I: The ratio of X to Y is between 0:100 and 20:80; R is a divalent group composed of monothiophene units or polythiophene units; R1 is 4-(2-hydroxy-2-methylpropionyl)phenoxyethyl; R2 is independently either a flexible chain alkyl group or a flexible chain ether group; In Formula II: r are each an independent integer from 1 to 8; R3 is or , Where m, a, b, c, and d are each independently selected from integers 2 to 6, and n, p, and q are each independently selected from integers 20 to 70. The weight ratio of compound II to compound I is 0.1:1 to 1.1:1.
[0010] In some implementations, R is independently selected from one of the following structural formulas: , In the structural formula Indicates the connection site.
[0011] In some implementations, R2 is independently selected from: or , Where r is selected from integers 1 to 4, x and y are each independently selected from integers 1 to 45, and r+x+y does not exceed 50; e and g are each independently selected from integers 2 to 6, f and h are each independently selected from integers 1 to 5, and j and k are each independently selected from integers 1 to 4.
[0012] In some implementations, R2 is independently selected from one of the following structural formulas: .
[0013] In some embodiments, R3 is selected from one of the following structural formulas: , Where n, p, and q are each independently selected from integers between 20 and 70.
[0014] In some embodiments, the molecular weight of the compound of formula I is 10,000-50,000 g / mol, preferably 30,000-40,000 g / mol.
[0015] In some embodiments, the molecular weight of the compound of formula II ranges from 10,000 to 30,000 g / mol.
[0016] In some embodiments, the composition further includes an organic solvent selected from at least one of chlorobenzene, dichlorobenzene, chloroform, dichloromethane, ethyl acetate, and propylene glycol methyl ether acetate.
[0017] On the other hand, this disclosure provides for the patterning application of the photoresist composition.
[0018] In some implementations, the patterning application includes: A photoresist film is formed on a substrate using the photoresist composition; The photoresist film is exposed; The exposed photoresist film is then developed.
[0019] In some implementations, the exposure is performed using deep ultraviolet or electron beam radiation.
[0020] In some embodiments, the developing agent used for developing is selected from at least one of chloroform, chlorobenzene, ethyl acetate, cyclohexanone, and dimethyl sulfoxide. Attached Figure Description
[0021] Figure 1 The mass spectrum of Formula II in Example 1 is shown.
[0022] Figure 2 This is a reduced density gradient plot from a molecular dynamics simulation of the two components in Example 1. Example 1 was selected as the model unit, and a visualization of its non-covalent interactions in real space was generated. A distinct green flake appears between the conductive and cross-linked phases, clearly indicating the weak interactions involved in their bonding.
[0023] Figure 3 The image shown is an atomic force microscope image of the pattern after exposure in Example 1, with a feature size of 10 μm.
[0024] Figure 4 The pattern shown is the result of Example 2. A 5×5 pentagram array with a feature size of 1 μm was designed, demonstrating the good patterning performance of Example 2 and proving that the two-component composition can achieve differences in solubility by constructing an interpenetrating cross-linked network.
[0025] Figure 5 The result is the pattern from Example 3. A 5×5 pentagram array with a feature size of 1 μm was designed. The pattern is clear and has high contrast, demonstrating a superior patterning capability compared to Example 2.
[0026] Figure 6 This is an optical microscope image of the electron beam exposure in Example 4. A 4×4 matrix composed of 1 μm lines with a 1:1 period was designed. Exposure voltage: 30 kV; initial exposure dose: 2 nC / cm.2 The initial dose has been exposed, demonstrating high sensitivity.
[0027] Figure 7 This is an optical microscope image of the electron beam exposure in Example 5. Since Example 5 does not contain photoinitiator side chains, a higher exposure dose (14 nC / cm²) can be observed in comparison. 2 This is used to achieve the patterning effect of the initial exposure matrix in Example 4.
[0028] Figure 8 The image shown is an atomic force microscope image obtained from electron beam surface exposure in Example 6. Based on normalized residual thickness analysis, the sensitivity was calculated to be 5 μC / cm. 2 The contrast ratio is 2.2.
[0029] Figure 9 The image shown in Example 7 is an atomic force microscope image obtained from electron beam surface exposure. Based on normalized residual thickness analysis, the sensitivity is calculated to be 17 μC / cm. 2 The contrast ratio is 1.7.
[0030] Figure 10 The image shown is an atomic force microscope image of the electron beam surface exposure in Example 8. Based on the normalized residual thickness analysis, the sensitivity is calculated to be 9 μC / cm. 2 The contrast ratio is 2.0.
[0031] Figure 11 This is a physical demonstration of the patterned pattern on a flexible polyimide film as shown in Example 1. The pattern maintains good stability even after bending.
[0032] Figure 12 The elastic modulus of Example 6 was tested by the continuous stiffness method of nanoindentation experiment, with an indentation depth of 20-40 nm as the effective range.
[0033] Figure 13 The hardness of Example 6 was tested by the continuous stiffness method of nanoindentation experiment, and the indentation depth of 20-40 nm was taken as the effective range.
[0034] Figure 14 The results of fatigue testing using nanoindentation experiments are shown in Example 6. The applied load was set to 300 μN, and the unloaded load was set to 30 μN. The cycle was 60 times.
[0035] Figure 15 The curve of the resistance change rate of the sensor under cyclic load in Example 11 is shown, where R is the real-time resistance and R0 is the initial resistance.
[0036] Figure 16The image shown in Comparative Example 1 is an atomic force microscope image obtained from electron beam surface exposure. Based on normalized residual thickness analysis, the sensitivity is calculated to be 32 μC / cm. 2 The contrast ratio is 1.4.
[0037] Figure 17 To illustrate the patterning results of Comparative Example 2 (with inert hydroxyl groups at the ends), a 5×5 pentagram array with a feature size of 1 μm was designed, and the pattern was completely washed away.
[0038] Figure 18A The results of ultraviolet light exposure at a wavelength of 365 nm are for Comparative Example 3.
[0039] Figure 18B The results are from deep ultraviolet light exposure at a wavelength of 254 nm.
[0040] Figure 19 For Comparative Example 4 (where the photocrosslinking functional group is an olefin), the elastic modulus was measured by the continuous stiffness method using nanoindentation experiments. The indentation depth of 20-40 nm was taken as the effective range.
[0041] Figure 20 For Comparative Example 4 (where the photocrosslinking functional group is an olefin), the hardness was tested by the continuous stiffness method of nanoindentation experiment, and the indentation depth of 20-40 nm was taken as the effective range.
[0042] Figure 21 The results of fatigue testing using nanoindentation are shown for Comparative Example 4 (photocrosslinked functional group is olefin). The loading load was set to 300 μN, and the unloading load was set to 30 μN. The cycle was 60 times. Detailed Implementation
[0043] To enable those skilled in the art to understand the features and effects of the present invention, the terms and expressions used in the specification and claims are explained and defined in general below. Unless otherwise specified, all technical and scientific terms used herein have the ordinary meaning understood by those skilled in the art regarding the present invention, and in case of conflict, the definitions in this specification shall prevail.
[0044] The theories or mechanisms described and disclosed herein, whether right or wrong, should not in any way limit the scope of the invention, that is, the contents of the invention can be implemented without being limited by any particular theory or mechanism.
[0045] In this document, the terms “contains,” “includes,” “containing,” and similar terms encompass the meanings of “basically composed of” and “composed of.” For example, when this document discloses “A contains B and C,” “A is basically composed of B and C” and “A is composed of B and C” should be considered as having been disclosed in this document.
[0046] In this document, all features defined in the form of numerical ranges or percentage ranges, such as numerical values, quantities, contents, and concentrations, are for the sake of brevity and convenience only. Accordingly, descriptions of numerical ranges or percentage ranges should be considered as covering and specifically disclosing all possible sub-ranges and individual numerical values (including integers and fractions) within those ranges.
[0047] In this document, when describing embodiments or examples, it should be understood that it is not intended to limit the invention to those embodiments or examples. Rather, all alternatives, modifications, and equivalents of the methods and materials described herein are covered within the scope defined by the claims.
[0048] For the sake of brevity, not all possible combinations of the technical features in each implementation or embodiment are described herein. Therefore, as long as there is no contradiction in the combination of these technical features, the technical features in each implementation or embodiment can be combined arbitrarily, and all possible combinations should be considered within the scope of this specification.
[0049] Unless otherwise specified, percentages, ppm, ppb, ppt and proportions in this article are all by weight.
[0050] In this article, hydrogen atoms include protium, deuterium, and tritium.
[0051] The photoresist of this application comprises a conjugated polymer (Compound I) as the conductive phase and a flexible polyether (Compound II) capped with 1,2-dithiocyclopentyl alkyl ester as the photocrosslinking phase. Without being limited to any particular theory, the applicant believes that the two components attract each other through van der Waals forces superimposed on sulfur and oxygen atoms to construct a physically interpenetrating crosslinked network. Through the construction of this nano-interpenetrating network, the introduced photoinitiator side chains (R1 side chains) achieve high exposure sensitivity by weakening the migration path of free radicals. Simultaneously, during exposure, disulfide bonds serve as photoreaction sites to construct a chemically crosslinked network. To date, no literature has disclosed the synergistic use of physically interpenetrating networks and chemical crosslinking in conductive photoresists.
[0052] In the photoresist compositions disclosed herein, the compound of formula I has the following structure: , This compound comprises alternating donor thiophene units and acceptor diketopyrrolopyrrole units, and has the lowest band gap compared to currently reported donor-acceptor conjugated organic polymers, resulting in excellent electrical conductivity.
[0053] In Formula I, R1 is 4-(2-hydroxy-2-methylpropionyl)phenoxyethyl, which is a side chain containing α-hydroxy ketone and belongs to the photoinitiator side chain.
[0054] R provides additional thiophene units, which can be monothiophene units or polythiophene units, wherein the polythiophene units comprise two or more units linked together by single bonds at the 2 and 5 carbon atoms of thiophene (unlike fused thiophene). Specifically, R may include 1 to 5 thiophene units, for example, 1, 2, 3, 4, 5, or any combination thereof, preferably 3, as shown in the following formula: .
[0055] The two Rs in Equation I can be the same or different, but they are preferred to be the same.
[0056] R2 is a flexible alkyl side chain or a flexible ether side chain. In some embodiments, R2 may be represented as: or , Where r is selected from an integer from 1 to 4 (e.g., a range consisting of 1, 2, 3, 4, or any two of them), preferably 1; x and y are each independently selected from an integer from 1 to 45 (e.g., a range consisting of 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24, 25, 26, 27, 28, 29, 30, 31, 32, 33, 34, 35, 36, 37, 38, 39, 40, 41, 42, 43, 44, 45, or any two of them), preferably 6-18, more preferably 8-16, and particularly preferably 10-14; r+x+y does not exceed 50 (e.g., 14, 15, 16, 17, 18, 19, 20, 21, 22, 23, 24). The range of integers 2-6 (e.g., 2, 3, 4, 5, 6 or any two of them), preferably 20-30, more preferably 22-28, more preferably 24-26; e and g are each independently selected from integers 1-5 (e.g., 1, 2, 3, 4, 5 or any two of them), preferably 1-3, more preferably 1-2; j and k are each independently selected from integers 1-4 (e.g., 1, 2, 3, 4 or any two of them), preferably 1-3, more preferably 1-2.
[0057] A more specific example of R2 is as follows: .
[0058] In Formula I, the ratio of X to Y is from 0:100 to 20:80, for example, 0:100, 1:99, 2:98, 3:97, 4:96, 5:95, 6:94, 7:93, 8:92, 9:91, 10:90, 11:89, 12:88, 13:87, 14:86, 15:85, 16:84, 17:83, 18:82, 19:81, 20:80 or any two of them; preferably 5:95 to 15:85, more preferably 8:92 to 12:88, and particularly preferably 10:90.
[0059] The molecular weight range of the compounds of Formula I is 10,000-50,000 g / mol (e.g., 12,000 g / mol, 14,000 g / mol, 16,000 g / mol, 18,000 g / mol, 20,000 g / mol, 22,000 g / mol, 24,000 g / mol, 26,000 g / mol, 28,000 g / mol, 30,000 g / mol, 32,000 g / mol, 34,000 g / mol, 36,000 g / mol, 38,000 g / mol, 40,000 g / mol, 42,000 g / mol, 44,000 g / mol, 46,000 g / mol, 48,000 g / mol, 50,000 g / mol, or any combination thereof), and more preferably 30,000-40,000 g / mol.
[0060] As a non-limiting example, the compound of formula I can be prepared by the following method: (1) Under inert gas protection, in an organic solvent, and in the presence of an alkali metal carbonate, 3,6-bis(5-bromothiophen-2-yl)-2,5-dihydropyrrolo[3,4-c]pyrrolo-1,4-dione reacts with 1-(4-(2-bromoethoxy)phenyl)-2-hydroxy-2-methylpropane-1-one to generate monomer 1: R1 is 4-(2-hydroxy-2-methylpropionyl)phenoxyethyl; (2) 3,6-Di(5-bromothiophene-2-yl)-2,5-dihydropyrrolo[3,4-c]pyrrolo-1,4-dione reacts with R2Br to generate monomer 2: , Where R2 is defined as in the compound of formula I above; (3) Under the protection of an inert gas, in an organic solvent, and in the presence of a catalyst, monomer 1 and monomer 2 react with ARA to produce compound I, wherein R is as defined above in combination with compound I, and A represents trialkylmethanetin alkyl.
[0061] In step (1) above, the inert gas is selected from nitrogen, argon, etc., the organic solvent is selected from N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMAc), etc., the alkali metal carbonate is selected from sodium carbonate, potassium carbonate, etc., and the reaction temperature is 100-150℃.
[0062] Monomer 2 in step (2) above can also be commercially available, for example 3,6-bis(5-bromothiophene-2-yl)-2,5-bis(2-decyltetradecyl)-2,5-dihydropyrrolo[3,4-c]pyrrolo-1,4-dione.
[0063] In step (3) above, the inert gas is selected from nitrogen, argon, etc., the organic solvent is selected from anhydrous toluene, etc., the catalyst is tris(dibenzylideneacetone)dipalladium(0) and tris(o-tolyl)phosphine, and the trialkyl methyltinyl group can be selected from trimethyl methyltinyl, triethyl methyltinyl, tripropyl methyltinyl, tributyl methyltinyl, etc.
[0064] Alternatively, an R1 group (4-(2-hydroxy-2-methylpropionyl)phenoxyethyl) can be introduced onto 3,6-bis(thiophene-2-yl)-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione, followed by bromination. An exemplary preparation process is as follows:
[0065] In the photoresist compositions disclosed herein, the compound of formula II has the following structure: .
[0066] Compound II is constructed from highly flexible and sterically hindrance-free long ether bonds and disulfide bonds, enabling flexible modification of rigid molecules and endowing materials with deformability. 1,2-Dithicyclopentane, as a preferred photocrosslinking group, can efficiently construct a flexible crosslinking network through ring-opening polymerization. During the material exposure stage, the conductive polymer structure and flexible components are in a "latent" state. Once the photoresist is exposed to radiation such as ultraviolet light or an electron beam, the hydroxyl-containing ketone side chains suspended in the conjugated organic polymer backbone rapidly cleave. The resulting free radicals can quickly attack the sulfur atoms of the disulfide bonds, inducing homolytic ring-opening, thereby completing the construction of a crosslinking network rich in disulfide bonds in a short time, and rapidly increasing the system's molecular weight.
[0067] In Formula II, r is an integer from 1 to 8 (e.g., a range consisting of 1, 2, 3, 4, 5, 6, 7, 8, or any two of them), preferably 2 to 6, more preferably 4; R3 is or , Wherein m, a, b, c, d are each independently selected from integers of 2 to 6 (e.g., 2, 3, 4, 5, 6 or any two of them), preferably 2 to 4, more preferably 2; n, p, and q are each independently selected from integers of 20 to 70 (e.g., 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70 or any two of them).
[0068] A more specific example of R3 is as follows: , Where n is selected from an integer between 20 and 70 (e.g., 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, or any combination thereof). The molecular weight range of the compound of Formula II is 10,000-30,000 (e.g., 12,000 g / mol, 14,000 g / mol, 16,000 g / mol, 18,000 g / mol, 20,000 g / mol, 22,000 g / mol, 24,000 g / mol, 26,000 g / mol, 28,000 g / mol, 30,000 g / mol, or any combination thereof), and more preferably 15,000-25,000 g / mol.
[0069] As a non-limiting example, the compound of formula II can be prepared by the following method: The organic solvent is selected from tetrahydrofuran (THF), anhydrous chloroform, etc., the nucleophilic catalyst is 4-dimethylaminopyridine, and the carboxylic acid activator is 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride. It is synthesized by reacting H-R3-H (i.e., diol) with 1,2-dithionylpentane acid at a temperature of 20-60℃.
[0070] The photoresist of this application can be obtained by dissolving the compound of Formula I and the compound of Formula II in an organic solvent in a certain proportion. The organic solvent can be selected from at least one of chlorobenzene, dichlorobenzene, chloroform, dichloromethane, ethyl acetate, and propylene glycol methyl ether acetate. In practice, the proportion of components of Formula I and Formula II can be adjusted, and the optimal proportion can be determined by the film retention rate of the patterned photoresist. The film retention rate refers to the proportion of the photoresist thickness retained after exposure and development, and is calculated using the following formula: (photoresist thickness after development / photoresist thickness before exposure) × 100%. In the photoresist composition, the weight ratio of compound II to compound I is from 0.1:1 to 1.1:1 (e.g., 0.2:1, 0.3:1, 0.4:1, 0.5:1, 0.6:1, 0.7:1, 0.8:1, 0.9:1, 1:1, 1.1:1 or any two of these), preferably from 0.7:1 to 1.1:1, more preferably from 0.8:1 to 1:1, and most preferably from 0.9:1.
[0071] The photoresist composition of this application can be used for patterning applications. In some embodiments, the patterning application may include: forming a photoresist film on a substrate using the photoresist composition; exposing the photoresist film; and developing the exposed photoresist film. The patterning application may also include pre-baking, post-baking, and other operations, which are known in the art. Exposure may be performed using deep ultraviolet or electron beam radiation, and the developer used for development may be selected from at least one of chloroform, chlorobenzene, ethyl acetate, cyclohexanone, and dimethyl sulfoxide.
[0072] In some exemplary embodiments, conductive glass, silicon wafers, ITO conductive films, or polyimide films are used as substrates. A photoresist solution is spin-coated onto the substrate at 2000-5000 rpm, and pre-baked at 40-80°C (e.g., 60°C) for 1-2 minutes to evaporate the solvent. Exposure experiments are performed using 200-400 nm ultraviolet light or an electron beam through a mask, causing a crosslinking reaction in the exposed areas. The exposure dose is 50-500 mJ / cm². 2 Or 5-50 μC / cm 2 Soak in a preferred organic solvent for 30-90 seconds. Remove and dry with nitrogen.
[0073] Compared with the prior art, the beneficial effects of the present invention are as follows: 1. Avoiding microphase separation of conjugated and non-conjugated components. Traditional patterning strategies include side-chain crosslinking and the introduction of crosslinking monomers. However, due to the significant differences in chemical structure, polarity, and conformation among the multiple components, these strategies lead to microphase separation at the nanoscale, ultimately resulting in patterns with defects such as increased roughness, jagged edges, bridging, or breakage. This invention constructs an interpenetrating network through physical crosslinking, effectively avoiding the non-uniformity caused by the separation and aggregation of conjugated and non-conjugated components.
[0074] 2. Shortening the free radical migration path and improving the exposure sensitivity of photoresist. The low sensitivity of conjugated polymers is due to the strong absorbance of conjugated molecular units, forming a dark film that weakens the light energy received by the active sites (photocrosslinked parts). Therefore, by interlocking the dual networks, the exposure groups are fixed near the side chains of the α-hydroxy ketone photoinitiator, thereby shortening the free radical migration path and improving the exposure efficiency.
[0075] 3. Avoiding the mismatch between rigid intramolecular structures and flexible device applications. Traditional conjugated organic molecular units inherently possess planar rigid fused ring structures, which facilitate intramolecular conjugation and strong π-π interactions, forming the basis for their high mobility. However, rigid structures pose a challenge to achieving reversible flexible deformation. The 1,2-dithioheterocyclic pentyl alkyl ester end-capping introduced in this invention forms highly flexible disulfide bonds after ring-opening polymerization, achieving flexible integration of the system by locking the semiconductor phase.
[0076] 4. Suitable for model photoresist research: Due to its well-defined molecular structure and simple synthesis process, the composition of this invention is very suitable as a model photoresist for studying advanced exposure mechanisms and photolithography techniques, providing strong support for the further development of photolithography technology.
[0077] 5. Broad Application Prospects: The photoresist composition provided by this invention is suitable for various photolithography technologies, including 254nm ultraviolet lithography, 365nm ultraviolet lithography, deep ultraviolet lithography, or electron beam lithography. The high-sensitivity photoresist composition can achieve a sensitivity of 20-60 μC / cm. 2 Its superior performance and broad application prospects make this invention have great potential in fields such as semiconductor manufacturing and micro / nano fabrication.
[0078] Example
[0079] The present invention will be described below by way of specific embodiments. It should be understood that these embodiments are merely illustrative and are not intended to limit the scope of the invention.
[0080] Unless otherwise specified, the equipment used in the following embodiments is conventional equipment in the art; unless otherwise specified, the reagents used are commercially available products or prepared by conventional methods in the art. In the following embodiments, unless otherwise described in detail, conventional experimental methods in the art can be used.
[0081] The main reagents used in the examples are as follows: 3,6-bis(5-bromothiophene-2-yl)-2,5-bis(2-decyltetradecyl)-2,5-dihydropyrrolo[3,4-c]pyrrolo-1,4-dione, 95%; 5-(1,2-dithioalkyl-3-yl)valeric acid, 98%; tris(dibenzylideneacetone)dipalladium, 98%; 5,5'-bis(trimethyltinyl)-2,2'-terthiophene, 98%; 3,6-bis(thiophene-2-yl)-2,5-dihydropyrrolo[3,4-c]pyrrolo-1,4-dione, 97%; N-bromosuccinimide, 99%; 4-methylaminopyridine, 98%; 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride, 98%; polyethylene glycol, 99%; ultra-dry N,N-dimethylformamide, analytical grade.
[0082] ¹H-NMR (400 MHz) analysis was performed using a Vaian DLG400 nuclear magnetic resonance spectrometer. Mass spectrometry analysis was performed using a Bruker Ultraflextreme MALDI mass spectrometer. Morphological evaluation of the lithographic pattern was performed using a Bruker Dimension Icon atomic force microscope (AFM). Optical microscope images were acquired using a Zeiss Axio Scope 5 system. Electron beam exposure was performed using a Hitachi SU8600 field emission scanning electron microscope in conjunction with a Raith ELPHY lithography module. The target pattern was designed and sized using KLayout software. Nanoindentation testing was performed using a BRUKER TI 980 nanomechanical testing system.
[0083] Preparation Example 1: Preparation of Compound I
[0084] (3,6-Di(5-bromothiophene-2-yl)-2,5-dihydropyrrolo[3,4-c]pyrrolo-1,4-dione) (2.4 g, 8 mmol) C 3.3 g (24 mmol) and 50 mL of dry N,N-dimethylformamide (DMF) were added to a 200 mL double-necked round-bottom flask. Nitrogen gas was bubbled through the reaction vessel for 20 minutes, and the mixture was heated to 120 °C and maintained at 1 hour. 2.4 mL (22.4 mmol) of 1-(4-(2-bromoethoxy)phenyl)-2-hydroxy-2-methylpropane-1-one was added dropwise to the reaction mixture using a syringe, and the mixture was stirred at 130 °C for 24 hours. The solution was cooled to room temperature and poured into 150 mL of water, then stirred for 30 minutes. The aqueous layer was separated using CHC. Extraction and merging of the organic layers using MgS After drying, the solvent was removed by rotary evaporation to obtain monomer 1. R1 is 4-(2-hydroxy-2-methylpropionyl)phenoxyethyl. 1 H NMR (600 MHz, CHCl3-d): δ 8.08 (m, 4H), 7.51 (d, J = 1.2 Hz, 2H), 7.06 (m, 2H), 6.96 (m, 4H), 4.27 – 4.11 (m, 6H), 4.03 – 3.99 (m, 2H), 3.91 –3.69 (m, 4H), 1.63 (d,J=5.2 Hz,12H).
[0085] Monomer 2 (3,6-bis(5-bromothiophen-2-yl)-2,5-bis(2-decyltetradecyl)-2,5-dihydropyrrolo[3,4-c]pyrrole-1,4-dione) is a commercially available product.
[0086] Monomer 1, monomer 2 (3,6-bis(5-bromothiophene-2-yl)-2,5-bis(2-decyltetradecyl)-2,5-dihydropyrrolo[3,4-c]pyrrolo-1,4-dione), and 5,5'-bis(trimethylstanyl)-2,2'-terthiophene (0.09 mmol) were added to a Schleck tube containing anhydrous toluene, degassed with nitrogen for 10 min, and then tris(dibenzylacetone)dipalladium(0) and tris(o-tolyl)phosphine were added and stirred at 110 °C under nitrogen for 12 h. The resulting green solution was poured into methanol and the precipitate was filtered. The polymer was purified using a Soxhlet extractor with methanol to remove oligomers and other impurities. The chloroform fraction was then precipitated in methanol and filtered. By adjusting the amounts of monomer 1 and monomer 2, polythiophene conjugated polymers of formula I with X:Y ratios of 0:100, 5:95, 10:90, and 20:80 were obtained, which are green solids.
[0087] Preparation Example 2: Preparation of Compound II
[0088] Polyethylene glycol (20000 g / mol) and thioctic acid ( The solution was dissolved in anhydrous chloroform, and 4-dimethylaminopyridine and 1-(3-dimethylaminopropyl)-3-ethylcarbodiimide hydrochloride were added. The mixture was stirred overnight at room temperature, and methanol was added for recrystallization to obtain the photocrosslinked polymer shown in Formula II. Its mass spectrum is shown below. Figure 1 As shown.
[0089] The photoresist was exposed using the component ratios and exposure methods described in the following embodiments. The photoresist solution was coated onto the silicon wafer surface, pre-baked at 60°C for 60 seconds, and then tested according to the following steps: (1) Spin-coating a solution of photoresist composition and solvent onto each silicon wafer, and then drying it to form a film.
[0090] (2) Expose the pattern as a line or gap under different exposure modes and gradually change the exposure amount.
[0091] (3) Immerse the silicon wafer in developing solution and observe the patterns on the silicon substrate under a microscope.
[0092] A linewidth resolution of 1 μm is considered the effective resolution. The minimum exposure dose of the photoresist, i.e., the sensitivity, is determined at this effective resolution.
[0093] Example 1
[0094] First, the polythiophene conjugated polymer prepared according to the method described in Preparation Example 1 was selected, with an X:Y ratio (i.e., the molar ratio of the initiator side chain to the alkyl side chain) of 10:90. The photocrosslinking polymer prepared in Preparation Example 2 and the polythiophene conjugated polymer were dissolved in a chloroform solution at a weight ratio of 0.5:1. The solution was stirred for 10 min and filtered through a 0.22 μm filter membrane. A coating was applied to a 1 cm silicon wafer at 4000 rpm, followed by pre-baking at 60°C for 1 min to evaporate the solvent. The electron beam exposure voltage was set to 30 kV, and the exposure dose was set to 20 μC / cm. 2 After exposure, the silicon wafer is immersed in cyclohexanone for 1 minute, then removed and dried with nitrogen gas. Figure 3 This is an atomic force microscopy (AFM) image of the 10 μm line pattern in Example 1. The results show a pattern thickness of 39 nm and a film retention rate of 20.7% (the pattern height before and after exposure was obtained using AFM, and then calculated according to the film retention rate formula). To investigate the interaction mechanism between the conductive phase and the crosslinked phase in this example, molecular dynamics simulations were performed. Its reduced density gradient diagram (…) Figure 2 The results show that a distinct green area appears at the interface between the two phases, indicating a strong non-covalent interaction between them. This interaction helps to form a stable interpenetrating network, thus achieving a good patterning effect.
[0095] Example 2
[0096] The difference between this embodiment and Example 1 lies in the ratio of the two components: the photocrosslinked polymer and the polythiophene conjugated polymer are dissolved in chloroform solution at a weight ratio of 0.7:1. The results show a pattern thickness of 106 nm and a film retention rate of 55.8%. The patterning result of the 5×5 star matrix is shown below. Figure 4 As shown.
[0097] Example 3
[0098] The difference between this embodiment and Example 1 lies in the ratio of the two components: the photocrosslinked polymer and the polythiophene conjugated polymer are dissolved in chloroform solution at a weight ratio of 0.9:1. The results show a pattern thickness of 188 nm and a film retention rate of 99%. The patterning result of the 5×5 star matrix is shown below. Figure 5 As shown.
[0099] As can be seen from the comparison of Examples 1, 2, and 3, the patterning performance of the two-component flexible conductive photoresist of the present invention is highly dependent on the ratio between the two components. With the increase of the proportion of the photocrosslinked polymer, its film retention gradually increases and reaches a stable level. In addition to the examples shown above, the applicant also tested multiple ratios of the weight ratio of the photocrosslinked polymer and the polythiophene conjugated polymer between 0.1:1 and 1.1:1. The results showed that at ratios less than 0.3:1, the pattern was completely washed away and not retained, while at ratios greater than 0.9:1, the pattern thickness remained relatively stable, reaching the optimal ratio. It is evident that photopatternability is highly dependent on the weight ratio between the two components, which needs to be within the range of 0.3 to 0.9. A ratio less than 0.3 will result in complete dissolution by the developer, while a ratio greater than 0.9 will lead to poor physical crosslinking before UV irradiation.
[0100] Example 4
[0101] The difference between this embodiment and Embodiment 3 lies in the control of the exposure process: an electron beam exposure mode is used, the exposure pattern is set as a matrix composed of 1μm lines with a 1:1 period, and the exposure voltage is 30 kV; the exposure doses of the 16 matrices are, in sequence: 2, 4, 6, 8, 10, 12, 14, 16, 18, 20, 22, 24, 26, 28, 30, 32 nC / cm. The exposure results are as follows: Figure 6 As shown (the above dosage and Figure 6 The matrix correspondence is as follows: from top to bottom, from left to right. The results show that in Example 4, the linewidth significantly increased at 4-8 nC / cm, and edge adhesion occurred. Beyond 10 nC / cm, adjacent patterns bridged, and localized resist layer detachment occurred. This example demonstrates that the upper limit dose of the photoresist line exposure process window in Example 3 is 1-2 nC / cm.
[0102] Example 5
[0103] The difference between this embodiment and Example 4 lies in the controlled ratio of the photoinitiator side chain and the alkyl side chain in the donor-acceptor conjugated polymer, where X:Y = 0:100. The exposure results are as follows... Figure 7 As shown in the figure, the results indicate that in Example 5, the linewidth significantly increased and edge adhesion occurred at 10-18 nC / cm, while adjacent patterns bridged and localized resist layer detachment occurred after exceeding 20 nC / cm. This example demonstrates that the upper limit dose of the photoresist's line exposure process window is 6-8 nC / cm.
[0104] Example 6
[0105] The difference between this embodiment and Embodiment 4 lies in the control of the exposure process: an electron beam surface exposure mode is used, the exposure pattern is set as a matrix of 3 μm squares, the exposure voltage is 30 KV, and the exposure dose is set to 1-49 μC / cm. 2 The exposure results are as follows Figure 8 As shown in the figure, the results indicate that the film undergoes chemical cross-linking with increasing exposure dose, which is retained after development. The first retained pattern appears at a dose of 5 μC / cm. 2 Below, the contrast ratio is 2.2 (a higher contrast ratio indicates better contrast). This embodiment demonstrates that the photoresist can be patterned using an electron beam, and its sensitivity is improved with the introduction of photoinitiator side chains.
[0106] The contrast parameters were determined by nonlinear fitting of the normalized residual thickness curve, and then... Calculation. In negative photoresist systems, D0 represents the sensitivity value, defined as the minimum exposure dose required to obtain the pattern. D 100 This represents the highest dose threshold that ensures the film remains unaffected during exposure. γ is the contrast value, reflecting the difference in distinguishability between the exposed and unexposed areas.
[0107] Example 7
[0108] The difference between this embodiment and Example 6 lies in the controlled ratio of the photoinitiator side chain and the alkyl side chain in the donor-acceptor conjugated polymer, with X:Y = 5:95. The exposure dose is set to 1-49 μC / cm. 2 The exposure results are as follows: Figure 9 As shown in the figure. The results indicate that the first retained pattern appears at a dose of 17 μC / cm. 2 The contrast ratio is 1.7. This embodiment demonstrates that it only has electron beam patterning capability, but its sensitivity and contrast are poor.
[0109] Example 8
[0110] The difference between this embodiment and Example 6 lies in the controlled ratio of the photoinitiator side chain and the alkyl side chain in the donor-acceptor conjugated polymer, where X:Y = 20:80. The exposure results are as follows... Figure 10 As shown in the figure. The results show that the first retained pattern appears at a dose of 9 μC / cm. 2 Below, the contrast ratio is 2.0. This embodiment demonstrates that when the photoinitiator side chain is in excess, a gradient crosslinking phenomenon occurs, leading to a decrease in sensitivity and contrast.
[0111] A comparison of Examples 4, 5, 6, 7, and 8 shows that the introduction of the photoinitiator side chain in this invention has a significant impact on the sensitivity and contrast of the conductive photoresist. On one hand, the photoinitiator side chain provides the system with more "photon absorption centers" and "reaction initiation points" per unit volume. At the same exposure dose, more active species can be generated, thereby reaching the reaction level required to induce a critical change in the solubility of the photoresist more quickly, thus requiring only a lower dose to complete the exposure. In particular, when the X:Y ratio is 0:100 (without photoinitiator) and 10:90, the sensitivity of the photoresist increases by 6-8 times with the increase of the photoinitiator content. On the other hand, comparing Examples 6, 7, and 8, excessive introduction can also lead to a large amount of light being absorbed when penetrating the top of the photoresist, causing uneven exposure between the top and bottom of the photoresist. This longitudinal non-uniformity "blurs" the critical boundary from solubility to insolubility during development, resulting in a decrease in contrast.
[0112] Table 1. Exposure metering and contrast ratios for Examples 6, 7, and 8
[0113] Example 9
[0114] This embodiment illustrates the patterning process of photoresist on a flexible polyimide film. First, the photoresist composition of Example 1 is spin-coated onto the flexible polyimide film. After soft baking, ultraviolet lithography is performed with an exposure dose of 120 mJ / cm², and a precise pattern is obtained using cyclohexanone developer. Figure 11 The pattern prepared by this process remains intact after being bent multiple times at a bending radius of 5 mm, without cracks or peeling, which proves that the photoresist can effectively meet the stringent requirements of flexible electronic devices for pattern accuracy and mechanical durability.
[0115] Example 10
[0116] To systematically evaluate the correlation between the mechanical properties of materials and their sensing applications, this embodiment, based on Example 6, introduces nanoindentation testing for in-depth analysis. Quantitative characterization results show that while maintaining an elastic modulus of 12.1 GPa (…),… Figure 12 At the same time, it possesses a significant hardness of 3.5 GPa. Figure 13 This unique combination of mechanical properties is crucial: the low modulus ensures that the material is prone to significant elastic deformation under external forces, thus making it sensitive to stress; while the high hardness endows the material with excellent resistance to plastic deformation and wear resistance, ensuring the mechanical stability and durability of the sensor during cyclic use.
[0117] Example 11
[0118] In the nanoindentation fatigue test disclosed herein, an indenter was used to perform a cyclic loading-unloading test on a 3 μm block of Example 6. For example... Figure 14 As shown in the cyclic load depth curve, when the maximum load reaches 300 mN, the indentation depth is 22 nm, and the residual depth after unloading is only 7 nm, with a calculated elastic recovery rate as high as 68.1%. Through 60 consecutive cycles of testing, the residual depth was found to stabilize with increasing cycle count, and the elastic recovery rate consistently remained above 60%, indicating that the material possesses excellent fatigue resistance and cyclic deformation stability, demonstrating significant elastic recovery capability at the nanoscale. This fatigue test strongly demonstrates the enormous potential of this material in realizing highly sensitive and long-life flexible sensors.
[0119] Example 12
[0120] The polythiophene conjugated polymer (X:Y=10:90) prepared according to the method of Preparation Example 1 and the photocrosslinked polymer prepared in Preparation Example 2 were mixed at a mass ratio of 1:1 and dissolved in chloroform. The prepared flexible conductive film sample was mounted on a dynamic fatigue testing machine and subjected to 30 cycles of tensile testing.
[0121] A precision digital multimeter was used to monitor and record the resistance change of the sample in real time during the cycling process. The initial resistance was denoted as... The real-time resistance during the cycle is denoted as R. Figure 15 The results are shown: the relative resistance of the sample (R / It exhibits excellent stability over 30 cycles.
[0122] Comparative Example 1
[0123] Side-chain comparison experiment of photoinitiator: The performance differences of the present invention in terms of photoresist sensitivity and contrast without photoinitiator side chains were compared. X:Y=0:100 was selected as the control group (Example 5), and tests were conducted under the same conditions as Example 6, using electron beam surface exposure mode with an exposure dose set to 1-97 μC / cm. 2 The exposure results are as follows Figure 16 As shown in the figure. The results show that the first retained pattern appears at a dose of 32 μC / cm. 2 At the same time, the contrast ratio was 1.4, which is significantly lower than that of Examples 6, 7 and 8, demonstrating the key role of the photoinitiator side chain in achieving high sensitivity.
[0124] Comparative Example 2
[0125] The photolithography process of Example 1 was repeated using PEG with inert hydroxyl-terminated ends instead of lipoic acid-terminated PEG. The results showed that after exposure, the material could not crosslink and completely dissolved in the developer, forming a 5×5 star-shaped matrix pattern. Figure 17 As shown, only a few traces were left, and a complete patterned structure was not formed. Comparing the results of Examples 1 and 2 demonstrates that introducing photocrosslinkable end groups into the PEG segments is a key prerequisite for realizing micro-nano patterning.
[0126] Comparative Example 3
[0127] This comparative example illustrates that when patterning is performed using photoresist compositions based on Formulas I and II, the choice of exposure light source wavelength has a decisive impact on pattern accuracy. The silicon wafer coated with the photoresist of Example 3 was placed on an exposure stage, covered with a mask, and exposed to light sources at 254 nm and 365 nm, respectively, with a dose set to 300 mJ / cm². -2 After exposure, isopropyl alcohol is used as the developer. If conventional 365 nm wavelength ultraviolet light is used for exposure (…), Figure 18A Because the absorption efficiency of α-hydroxyketone molecules at this wavelength is significantly lower than their absorption peak (240-260 nm), the effective optical contrast of the photoresist system is significantly reduced. The direct consequence is insufficient difference in dissolution rates between the exposed and unexposed areas during the exposure process, ultimately leading to a decrease in the overall accuracy and fidelity of the pattern. In contrast, using a 254 nm wavelength exposure that matches the absorption peak of the photoinitiator can achieve a more efficient and uniform photolysis reaction at the same dosage, thereby obtaining high-quality patterns with sharp edges and precise linewidths. Figure 18B This comparative example demonstrates that optimizing the exposure wavelength is key to achieving high-precision micromachining of flexible electronics for a specific photoresist chemical system.
[0128] Comparative Example 4
[0129] In this comparative example, PEG with photoactive terminal functional groups was used instead of PEG capped with thioctic acid, and the photolithography process of Example 1 was repeated for patterning. The elastic modulus and hardness were 85.3 GPa, respectively. Figure 19 ) and 10.2 GPa ( Figure 20 Excessively high modulus cannot achieve small strains and is incompatible with flexible substrates. Figure 21 Typical load-displacement curves for this material are shown. When the indenter is unloaded at its maximum depth, the material exhibits significant permanent deformation with an extremely high residual depth. Calculations show that its elastic recovery rate is only about 11%. This indicates that the deformation generated under stress is mostly irreversible plastic deformation, lacking the elasticity necessary for a flexible sensing material. The residual depth accumulation of Comparative Example 4 (alkenyl) is significantly higher than that of Example 1 (dithiopentanyl) because its static network accumulates irreversible damage under cyclic stress.
[0130] The comparison between Comparative Example 4 (static crosslinking of olefins) and Example 1 (dynamic crosslinking of disulfide bonds) shows that although static covalent crosslinking provides basic elasticity, its network is prone to irreversible fracture under cyclic loading, leading to cumulative plastic deformation and performance degradation. In contrast, the dynamic disulfide bond crosslinking network used in this application can effectively dissipate input energy and avoid stress concentration through reversible fracture and recombination. This not only endows the material with higher toughness and fatigue resistance but also ensures the stability and reliability of the conductive network under long-term, cyclic deformation.
[0131] The specific embodiments of this disclosure have been described above. The scope of protection of this disclosure is not limited to the exemplary embodiments described above. Any modifications, equivalent substitutions, or improvements made by those skilled in the art within the spirit and principles of this disclosure should be included within the scope of protection of this disclosure.
Claims
1. A photoresist composition, characterized in that, The photoresist composition comprises compounds of formula I and formula II: (I) (II) In Formula I: The ratio of X to Y is between 1:99 and 20:80; R is a divalent group composed of monothiophene units or polythiophene units; R1 is 4-(2-hydroxy-2-methylpropionyl)phenoxyethyl; R2 is independently either a flexible chain alkyl group or a flexible chain ether group; In Formula II: r are each an independent integer from 1 to 8; R3 is or , Where m, a, b, c, and d are each independently selected from integers 2 to 6, and n, p, and q are each independently selected from integers 20 to 70. The weight ratio of compound II to compound I is 0.1:1 to 1.1:
1.
2. The photoresist composition according to claim 1, characterized in that, The ratio of X to Y is between 5:95 and 15:
85.
3. The photoresist composition according to claim 1, characterized in that, The ratio of X to Y is between 8:92 and 12:
88.
4. The photoresist composition according to claim 1, characterized in that, The ratio of X to Y is 10:
90.
5. The photoresist composition according to claim 1, characterized in that, R is independently selected from one of the following structural formulas: , In the structural formula Indicates the connection site.
6. The photoresist composition according to claim 1, characterized in that, R2 is selected independently from: or , Where r' is selected from integers 1-4, x and y are each independently selected from integers 1-45, and r'+x+y does not exceed 50; e and g are each independently selected from integers 2-6, f and h are each independently selected from integers 1-5, and j and k are each independently selected from integers 1-4.
7. The photoresist composition according to claim 1, characterized in that, R2 is independently selected from one of the following structural formulas: 。 8. The photoresist composition according to claim 1, characterized in that, R3 is selected from one of the following structural formulas: , Where n, p, and q are each independently selected from integers between 20 and 70.
9. The photoresist composition according to claim 1, characterized in that, The molecular weight of the compound of formula I is 10,000-50,000 g / mol; and / or The molecular weight range of compounds of formula II is 10,000-30,000 g / mol.
10. The photoresist composition according to claim 1, characterized in that, The molecular weight of the compound of formula I is 30,000-40,000 g / mol.
11. The photoresist composition according to claim 1, characterized in that, The composition further includes an organic solvent selected from at least one of chlorobenzene, dichlorobenzene, chloroform, dichloromethane, ethyl acetate, and propylene glycol methyl ether acetate.
12. Patterning application of the photoresist composition according to any one of claims 1-11.
13. The patterning application according to claim 12, characterized in that, The patterning applications include: A photoresist film is formed on a substrate using the photoresist composition; The photoresist film is exposed; The exposed photoresist film is then developed.
14. The patterning application according to claim 13, characterized in that, Exposure is performed using deep ultraviolet or electron beam radiation; and / or The developing agent used is selected from at least one of chloroform, chlorobenzene, ethyl acetate, cyclohexanone, and dimethyl sulfoxide.
Citation Information
Patent Citations
Polymer semi-conductive photoresist with side chain containing azide group as well as preparation method and application of polymer semi-conductive photoresist
CN114479020A
Photosensitive conductive photoresist, preparation method thereof and photoetching patterning process based on photoresist
CN116699942A